GAME ADVENTURE UNTUK PEMBELAJARAN PENGGUNAAN HATSUON PADA MATA KULIAH HANASHIKATA - Marina Indahningrum (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2019)
Nowadays technology is increasingly developing so that everyone must be able to use various technologies to meet their needs, especially in midwives education. As a lecturer, it is expected to be able to keep abreast of rapid technological developments, sometimes even as students, it feels to be more professional in using technology today. So many students who feel less motivated by learning that is not interesting. Therefore this research is in the form of an Android-based Japanese educational game application that will be applied to one of the Japanese language majors, namely speaking or Hanashikata. This research uses a game that will make it easier for students to learn Japanese. The adventure game is an adventure-based game that is given an educational element. The education included is learning how to pronounce Japanese. This game is a solution to overcome the obstacles of teaching methods that are less fun, while Japanese language enthusiasts more and more. In this study, we discussed how to apply this adventure game application as a learning medium in one course, where students will learn learning material not only with the help of lecturers or modules but with the context in the game. Based on the design of the game made it can be felt this game will provide high motivation to learn for students and provoke their curiosity and creativity.